2009
DOI: 10.1007/s12032-009-9273-1
|View full text |Cite
|
Sign up to set email alerts
|

Biological characteristics of a specific brain metastatic cell line derived from human lung adenocarcinoma

Abstract: To study the expression of VEGF, MMP-9, EGFR, and S100B in a highly brain metastases sub-clone cell line, PC14/B. The in vitro metastases-related behaviors of PC14 /B cells, such as adhesion to extracellular matrix (ECM), migration, and invasion were determined and compared with primary PC14 cells and A549 cells that do not metastasize to brain. The expression of vascular epithelial growth factor (VEGF), matrix metalloproteinase 9 (MMP-9), S100B, and epidermal growth factor receptor (EGFR) in the above three c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Previously, we established PC14/B cell line, which possesses a notable property of brain metastasis compared with primary parental PC14 cells and lung adenocarcinoma cell line A549, and further demonstrated that the expressions of S100B, VEGF and MMP‐9 were much higher in PC14/B cells than in PC14 and A549 cells . In the present study, we employed siRNA technique to knockdown S100B in PC14/B cell line and found that depletion of S100B in PC14/B cells led to significant decrease in cell proliferation and colony formation ability, indicating that S100B could promote the growth of PC14/B cells.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Previously, we established PC14/B cell line, which possesses a notable property of brain metastasis compared with primary parental PC14 cells and lung adenocarcinoma cell line A549, and further demonstrated that the expressions of S100B, VEGF and MMP‐9 were much higher in PC14/B cells than in PC14 and A549 cells . In the present study, we employed siRNA technique to knockdown S100B in PC14/B cell line and found that depletion of S100B in PC14/B cells led to significant decrease in cell proliferation and colony formation ability, indicating that S100B could promote the growth of PC14/B cells.…”
Section: Discussionmentioning
confidence: 57%
“…PC14/B cell line has been employed as a model of specific brain metastasis of lung adenocarcinoma, and it was established by the intravenous inoculation of human lung adenocarcinoma PC14 cells into nude mouse and the selection of the clones that metastasize to the mouse brain . We previously reported that S100B was highly expressed in the PC14/B cells compared with the parental PC14 cells and the lung adenocarcinoma cell line A549 . However, the exact role of S100B in brain metastasis of lung adenocarcinoma is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the expression of CD44 (3) and chemokine receptor-4 (4) on the surface of NSCLC cells is thought to contribute to lung cancer cell metastasis to the brain. Matrix metalloproteinase (MMP)-9 has been reported to be specifically overexpressed by brain metastases originating in lung adenocarcinomas, suggesting a significant role of MMP-9 in the transmigration of the tumor cells across the blood vasculature into the brain parenchyma (5). In addition, a series of studies implicated growth factors in NSCLC brain metastases (6,7).…”
mentioning
confidence: 99%
“…In addition, MMP-1 and MMP-9 were shown to be overexpressed in brain-seeking breast cancer cells in comparison with bone-seeking variants [107], while expression of MMP-2 and MMP-9 was found to be upregulated in breast cancer cells treated with angiotensin II, probably contributing to the increased migration through brain endothelial cells [108]. MMP-9 was found to be overexpressed by brain metastatic lung adenocarcinoma cells [109].…”
Section: The Role Of Matrix Metalloproteinases In the Formation Of Brmentioning
confidence: 95%